TECHNOLOGY OF CODING OF BLOCKS OF AN AERIAL PHOTOGRAPH TAKING INTO ACCOUNT SEMANTICALY IMPORTANT INFORMATION TO AIRBORNE SYSTEMS FOR AIR MONITORING - Баранник, Володимир Вікторович; Мусієнко, Олександр Павлович; Леках, Альберт Анатолійович (Science-based technologies, 2016)
In article the questions connected with onboard processing of digital aerial images obtained during air monitoring. Digital aerial images are characterized by different semantic richness. Therefore, special attention in the processing of the aerial photographs should be given the choice of semantic saturation, in is the most significant information about the contours and object boundaries areas. This approach will further reduce the processing time during the coding stage, but may raise issues associated with the loss of significant information. It is therefore proposed to reduce the amount of transmitted data to consider the degree of acceptable loss of quality of information on key features of interpretation. Shows a diagram of the technology coding of blocks of aerial photographs to highlight semantically important information. It justifies the main stages of coding technology blocks the aerial view on board of the unmanned aircraft.